EXPERIMENTAL STUDY OF BEHAVIOR OF BAMBOO REINFORCED CONCRETE BEAMS - Malokar, Amogh; Naktode, Dr. P. L. (IJRDO - Journal of Mechanical And Civil Engineering, 2022)
The importance of bamboo as a sustainable material is gradually increasing in the construction sector. It is rapidly becoming a concerned area of research, either as a construction material or alternative replacement to steel. This study involves use of bamboo as an alternative to steel reinforcement in concrete beams and its comparative analysis with reinforced cement concrete beams. The present study involves casting of 15 beams i.e., 3 RCC, 3 BSRCC & 9 BRCC. The reinforcement used in BRCC beams had an average dimension of 20 mm x 8 mm and were divided into plain, coated-plain & coated-grooved types. The beams were subjected to four-point loading using universal testing machine. The results of casting suggested that BRCC beams sustain better load and deflection than RCC beams.